How might values in mathematics learning affect the development of beliefs: An exploratory study with Chinese elementary students. Issue 1 (March 2022) - Seah, Wee Tiong; Pan, Yichen; Zhong, Juan
258 Grade 3 students in a suburban primary school located in Chengdu, China responded to an open-ended questionnaire item regarding their beliefs about mathematics. The traditional beliefs attracted the most number of students, followed by integral, feeling good, and constructivist beliefs. Since the questionnaire also identified the students' values in relation to positive mathematical wellbeing, it was additionally found that students who valued engagement highly were more likely to hold constructivist beliefs and less likely to hold traditional beliefs, compared to peers who did not value engagement as highly. Also, students who valued perseverance highly were more likely to hold integral beliefs.